2021
DOI: 10.1080/26410397.2021.1921901
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and opportunities: a qualitative study of the experiences of abortion centre staff with abortion care during the first COVID-19 lockdown in Flanders, Belgium

Abstract: The COVID-19 pandemic and corresponding measures impacted the organisation of services for abortion on request in Flanders, Belgium. This study describes abortion centre staff's perceptions of the influence of protective measures on abortion consultations and procedures, and aims to identify obstacles and opportunities that arose from this situation. Through the anonymised patient records of one Flemish abortion centre, we compared the number of requests and abortions during the first lockdown (16 March-14 Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…Similarly, as participants gained experience, they became more confident in their ability to safeguard patients by identifying those who were experiencing coercive control or domestic violence. The importance of experience in mitigating concerns among ACPs was a finding of the Belgian study 27 ; participants initially expressed concern that a reduction in in-person contact would be emotionally detrimental for patients; however, they reported that their ability to conduct telephone consultations improved as they gained experience. The NHS Lothian clinic leadership structures, including clear routes to accessing senior nursing and medical advice to support these decisions, were also identified as facilitators of safe telemedicine abortion care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, as participants gained experience, they became more confident in their ability to safeguard patients by identifying those who were experiencing coercive control or domestic violence. The importance of experience in mitigating concerns among ACPs was a finding of the Belgian study 27 ; participants initially expressed concern that a reduction in in-person contact would be emotionally detrimental for patients; however, they reported that their ability to conduct telephone consultations improved as they gained experience. The NHS Lothian clinic leadership structures, including clear routes to accessing senior nursing and medical advice to support these decisions, were also identified as facilitators of safe telemedicine abortion care.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge this is the first study to explore ACP perspectives of abortion care provision via telemedicine in the UK medicolegal context during COVID-19. There have been few other studies23 24 27 exploring ACP perspectives on the provision of telemedicine abortion care – two in the USA, both of which were prior to COVID-19, and one in Belgium during the COVID-19 pandemic. The telemedicine models and medicolegal contexts in these studies are different from the current UK setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 34 87 Access to postabortion care was negatively impacted as reported in China, 93 Ethiopia, 52 Uganda 53 and Belgium. 89 Two studies described an increase in abortion service utilisation at tertiary care facilities in the US 49 and among teenagers in Ethiopia. 68 Decreases in access or utilisation of remote or partially remote abortion services were described by three studies.…”
Section: Safe Abortion Servicesmentioning
confidence: 99%
“…68 Decreases in access or utilisation of remote or partially remote abortion services were described by three studies. 88 89 108 Endler et al and DeKort et al observed declines in at-home medical abortion utilisation, and Aiken et al 90 found that telemedicine abortion requests through Women on Web, an online telemedicine abortion service, increased significantly in Portugal, Italy, Hungary, Malta and Northern Ireland, while they decreased significantly in the UK. This decrease is speculated to be caused by a change in abortion legislation in the UK, whereby access to no-test abortions through the formal health sector significantly increased.…”
Section: Safe Abortion Servicesmentioning
confidence: 99%